Conference on Sparrows, 20th March 2009, Pisa, Italy - Dinetti, Marco (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
"Passeri in crisi?" Da "pest" a "species of conservation koncern": biologia, problematiche e conservazione dei passeri" was the title of the Conference on Sparrows held in Pisa (Italy) on 20th March 2009.
Keywords: wróblowe; konferencja; czasopismo